Evaluasi Kesesuaian Lokasi Tempat Penampungan Sampah Sementara di Kecamatan Subang - Arya juliansyah; Tarlani Tarlani (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. The accumulation of waste in Subang Subdistrict disturbs the comfort of the community because waste production is increasing while infrastructure is inadequate. This study aims to evaluate the suitability of TPS locations in Subang District based on SNI 3242 2008 and PERMEN PU 03 2013. Quantitative descriptive research method was used with technical and non-technical variables, then scoring was done on each variable to produce output. The results of the analysis show that TPS infrastructure in Subang Sub-district is still inadequate. Of the 8 TPS locations, only 2 units meet national standards and ministerial regulations. Based on community perceptions, the average assessment of TPS is 30.75, including the unfit category. Follow-up from the technical and non-technical evaluation analysis showed that 3 polling stations will be retained, while the other 5 polling stations will be relocated to areas that are not accessible. The area of land suitable for TPS in Subang Sub-district is 857 hectares. Land that includes suitable locations can be considered for the placement of new TPS. This study provides recommendations for the improvement and equalization of TPS facilities to improve the comfort and cleanliness of the environment in Subang District. Abstrak. Penumpukan sampah di Kecamatan Subang mengganggu kenyamanan masyarakat karena produksi sampah meningkat sementara prasarana tidak memadai. Penelitian ini bertujuan mengevaluasi kesesuaian lokasi TPS di Kecamatan Subang berdasarkan SNI 3242 2008 dan PERMEN PU 03 2013. Metode penelitian deskriptif kuantitatif digunakan dengan variabel teknis dan non-teknis, kemudian dilakukan skoring pada setiap variabel untuk menghasilkan output. Hasil analisis menunjukkan bahwa prasarana TPS di Kecamatan Subang masih kurang memadai. Dari 8 lokasi TPS, hanya 2 unit yang memenuhi standar nasional dan peraturan menteri. Berdasarkan persepsi masyarakat, rata-rata penilaian terhadap TPS adalah 30,75, termasuk kategori tidak layak. Tindak lanjut dari analisis evaluasi teknis dan non-teknis menunjukkan 3 TPS akan dipertahankan lokasinya, sedangkan 5 TPS lainnya akan direlokasi ke daerah yang tidak terjangkau TPS. Luas lahan yang sesuai untuk TPS di Kecamatan Subang adalah 857 hektar. Lahan yang termasuk lokasi layak dapat dipertimbangkan untuk penempatan TPS baru. Penelitian ini memberikan rekomendasi untuk peningkatan dan pemerataan fasilitas TPS guna meningkatkan kenyamanan dan kebersihan lingkungan di Kecamatan Subang. .